RNA-Seq Analysis of the Response of the Halophyte, Mesembryanthemum crystallinum (Ice Plant) to High Salinity - Tsukagoshi, Hironaka; Suzuki, Takamasa; Nishikawa, Kouki; Agarie, Sakae; Ishiguro, Sumie; Higashiyama, Tetsuya (PLOS ONE, 2015)
Understanding the molecular mechanisms that convey salt tolerance in plants is a crucial issue for increasing crop yield. The ice plant (Mesembryanthemum crystallinum) is a halophyte that is capable of growing under high salt conditions. For example, the roots of ice plant seedlings continue to grow in 140 mM NaCl, a salt concentration that completely inhibits Arabidopsis thaliana root growth. Identifying the molecular mechanisms responsible for this high level of salt tolerance in a halophyte has the potential of revealing tolerance mechanisms that have been evolutionarily successful. In the present study, deep sequencing (RNAseq) was used to examine gene expression in ice plant roots treated with various concentrations of NaCl. Sequencing resulted in the identification of 53,516 contigs, 10,818 of which were orthologs of Arabidopsis genes. In addition to the expression analysis, a web-based ice plant database was constructed that allows broad public access to the data. The results obtained from an analysis of the RNAseq data were confirmed by RT-qPCR. Novel patterns of gene expression in response to high salinity within 24 hours were identified in the ice plant when the RNAseq data from the ice plant was compared to gene expression data obtained from Arabidopsis plants exposed to high salt. Although ABA responsive genes and a sodium transporter protein (HKT1), are up-regulated and down-regulated respectively in both Arabidopsis and the ice plant; peroxidase genes exhibit opposite responses. The results of this study provide an important first step towards analyzing environmental tolerance mechanisms in a non-model organism and provide a useful dataset for predicting novel gene functions.